Semi-Peripheral Russia and the Ukraine Crisis. Issue 4 (1st October 2016) - Dzarasov, Ruslan
ABSTRACT: The nature of Russia's nascent capitalism defines its Russian foreign policy and particularly its involvement in the Ukraine crisis. The author rejects the "two imperialisms" thesis concerning East-West confrontation. He departs from the world-system approach and defines Russian capitalism as a semi-periphery of the world system. This means that Russia is half-dependent on the West. On the other hand, it is able to challenge Western hegemony on certain issues. The nature of the country's big business is seen as short-term, rent-seeking behaviour, inconsistent with sound investment and long-term development. Atomisation of the ruling class creates preconditions for a strong authoritative state. However, the Russian ruling elite is deeply split into two factions: one oriented to integration with the West (comprador elite) and the other favouring the strengthening of independent Russian capitalism. Russian foreign policy is shaped by the opposition and compromises between these two groups. That is the reason why it is so inconsistent and contradictory. Particularly in Ukraine, Russia tries to withstand Western challenge, but leaves open options for accommodation. The Russian attempt to make the West regard its national interests within the framework of the current world order, according to the present paper, is doomed to failure.